Catholicism the story of Catholic Christianity - O'Collins, Gerald 1931-; Farrugia, Mario 1955- (2015)
This book explains how Roman Catholicism and its beliefs and practices came to be what they are. The authors move through history to sum up the present characteristics of Catholic Christianity and the major tests it faces in the third millennium. Explaining matters in a fresh and original way, they do justice to the Catholic heritage and show that Catholicism is a dynamic and living faith. Well-structured, highly informative, and clearly written, the book does not evade critical problems and the negative side of history. Rather, O'Collins and Farrugia explore challenges facing Catholics and other Christians and engage with contemporary moral issues. ...Book cover
Includes bibliographical references
Keywords: Katholische Kirche; Catholic Church -- Doctrines; Catholic Church -- Doctrines -- History; Geschichte; Kirchengeschichte; Church history; Katholische Theologie; Katholizismus